Microlearning Instructional Design with Process Approach for Improving Early Reading Skills of Prospective Elementary School Teachers - Bagus Cahyanto; Titis Angga Rini; Evi Rizqi Salamah; Muhammad Ali Rohmad (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractTeaching early reading is a crucial skill for prospective elementary school teachers. However, in practice, there is a persistent observation of a low mastery of teaching methods in this area which is a mandatory pedagogical competency for teachers. This study aimed to describe the improvement of college students' proficiency in teaching early reading through microlearning-based instructional design with a process approach. The process approach refers to the implementation of the stages of reading instruction, namely in the pre-reading, during reading and post-reading stages. This study uses quantitative and qualitative data through tests, field notes, and documentation. The N-Gain test was utilized to analyze the quantitative data, employing one-group pretest and posttest design. Concurrently, the qualitative data from field notes and documentation underwent analysis through display, reduction, and verification data. The results of this study indicate that the implementation of microlearning-based instructional design with a process approach significantly enhances the early reading teaching skills of prospective elementary school teachers. Notably, improvements are observed across in the pre-reading, during-reading, and post-reading stages. The impact is particularly pronounced in the during-reading stage, where collage students exhibit enhanced mastery of teaching methods and adept use of appropriate media. The conclusion of this study shows the efficacy of an instructional design tailored to and focused on the specific needs of learning segments, which provides a better learning experience in teaching early reading.Keywords: early reading, instructional design, microlearning, process approach. AbstrakPengajaran membaca permulaan menjadi salah satu kompetensi yang harus dikuasi mahasiswa calon guru sekolah dasar meskipun dalam praktiknya, ada pengamatan terus-menerus tentang penguasaan metode pengajaran yang rendah di area ini yang merupakan kompetensi pedagogik wajib bagi guru. Penelitian ditujukan untuk mendeskripsikan peningkatan keterampilan mahasiswa dalam pengajaran membaca permulaan melalui desain instruksional berbasis microlearning dengan pendekatan proses. Pendekatan proses ini mengacu pada penerapan tahapan pengajaran membaca yakni dalam tahap pra, saat, dan pasca membaca. Penelitian ini menggunakan data kualitatif dan kuantitatif dengan pengumpulan datanya melalui tes, catatan lapangan, dan dokumentasi. Hasil datanya dianalisis dengan statistik deskriptif melalui uji N-Gain berdasarkan hasil tes dari one group pretest and postest design. Analisis juga dilakukan melalui data display, reduksi, dan verifikasi untuk hasil catatan lapangan dan dokumentasi. Hasil penelitian ini menunjukkan bahwa desain instruksional berbasis microlearning dengan pendekatan proses dapat meningkatkan keterampilan pengajaran membaca permulaan mahasiswa calon guru sekolah dasar dalam kategori cukup signifikan. Peningkatan ini meliputi pengajaran pada tahap pra, saat, dan pasca membaca permulaan khususnya pada tahap saat membaca dalam penguasaan metode dan penggunaan media yang tepat. Kesimpulannya menunjukkan bahwa desain intruksional yang didesain secara khusus dan terfokus dalam segmen-segmen pembelajaran memberikan pengalaman belajar yang lebih baik pada mahasiswa dalam pengajaran membaca permulaan.Kata kunci: desain intruksional, membaca permulaan, microlearning, pendekatan proses.